Bargaining over Residential Real Estate: Evidence from England - Antonio M. Merlo; François Ortalo-Magné (Center for Economic Studies and ifo Institute (CESifo), 2002)
This paper presents and investigates a new data set of individual residential property transactions in England. The main novelty of the data is the record of all listing price changes and all offers made on a property, as well as all the visits by potential buyers for a subset of the properties. We analyze individual seller and potential buyers behavior within property transaction histories. This leads us to establish a number of stylized facts pertaining specifically to the timing and terms of agreement in housing transactions, and more generally, to the sequence of events that occur from initial listing to sale agreement. We assess the limitations of existing theories in explaining the data and propose an alternative theoretical framework for the study of the strategic interactions between buyers and sellers that is consistent with the empirical evidence.
Keywords: D40; L00; R00; 330